Tele-intensivists can instruct non-physicians to acquire high-quality ultrasound images - Levine, Andrea R.; McCurdy, Michael T.; Zubrow, Marc T.; Papali, Alfred; Mallemat, Haney A.; Verceles, Avelino C. (Journal of critical care, 2015)
Intensive care unit telemedicine (tele-ICU) uses audiovisual systems to remotely monitor and manage patients. Intensive care unit ultrasound can augment an otherwise limited bedside evaluation. To date, no studies have utilized tele-ICU technology to assess the quality and clinical use of real-time ultrasound images. We assessed whether tele-intensivists can instruct nonphysicians to obtain high-quality, clinically useful ultrasound images. This prospective pilot evaluated the effectiveness of a brief educational session of nonphysician “ultrasonographers” on their ability to obtain ultrasound images (right internal jugular vein, bilateral lung apices and bases, cardiac subxiphoid view, bladder) with real-time tele-intensivist guidance. All ultrasound screen images were simultaneously photographed with a 2-way camera and saved on the ultrasound machine. The tele-intensivist assessed image quality, and an independent ultrasound expert rated their use in guiding clinical decisions. The intensivist rated the tele-ICU camera images as high quality (70/77, 91%) and suitable for guiding clinical decisions (74/77, 96%). Only bilateral lung apices demonstrated differences in quality and clinical use. All other images were rated noninferior and clinically useful. Tele-intensivists can guide minimally trained nonphysicians to obtain high-quality, clinically useful ultrasound images. For most anatomic sites, tele-ICU images are of similar quality to those acquired directly by ultrasound.